Ancient olive trees as a source of olive oils rich in phenolic compounds. (15th March 2019) - Rodrigues, Nuno; Casal, Susana; Pinho, Teresa; Peres, António M.; Bento, Albino; Baptista, Paula; Pereira, José Alberto
Highlights: Olive oil phenolics from centenarian trees were evaluated during 4 harvest seasons. Statistical analysis discriminate olive oils by total phenols levels. Half of the specimens produced oils that were able to consistently fulfill olive oils' health claim. Some trees gave high phenolic contents being potential candidates for breeding. Individual phenolic contents separate olive oils by crop year. Abstract: Olive oil phenolic compounds are receiving increased attention due to its influence on sensory characteristics and to scientific evidences of positive health effects. In this work, 28 ancient olive trees were selected and, during four consecutive seasons (2014–2017), oils were extracted and their phenolic fraction characterized. Hydroxytyrosol and tyrosol secoiridoids were the predominant groups, with contents between 32 and 496 mg of tyrosol equivalents/kg. Based on principal component analysis it could be concluded that the individual phenolic contents enabled the unsupervised grouping of olive oils by crop year. Furthermore, linear discriminant analysis allowed achieving sensitivities greater than 90%. It was shown that some specimens consistently allowed obtaining oils with high phenolic contents (≥500 mg tyrosol equivalents/kg). The identification of centenarian specimens for breeding based on their potential to produce oils with high levels of healthy compounds is of utmost interest, contributing to preserve the genetic heritage.